Peacebuilding Framework For Business: Role Of Small To Medium-sized Private Enterprises In Post-conflict Economic Recovery In Central Africa - Fujimura, Yoko (2021)
Considering the private sectors are responsible for 90 per cent of employment in the world and the majority of the sectors consist of small businesses, it is inevitable to engage them to achieve sustainable development and peace. Despite the UN-led initiatives, the absence of practical guidance on how they can contribute to the initiative remains a challenge. This study aims at establishing a framework for public, private and non-profit sectors to contribute to economic recovery as part of peacebuilding. This study especially tries to propose an operational framework for Chad, which can be modified in the countries that are also suffering from massive displacement, lack of national budget and decreasing international aid. Based on the pre-established conceptual framework, this study examines if the pre-identified variables are sufficient to guide the relevant actors to pursue the private sector engagement in economic recovery and peacebuilding. This study concludes that having an operational PPP will lead to sustainable economic recovery and peace with mediating variables (policy and guidelines, research and reports on best practices and lessons learnt, clear understanding of roles and responsibilities, as well as the mandated Resident Coordinator), and the moderating variables (formalization of informal business, capacity development, accessible information, international recognition and shared value with an integrated partnership